CONTRIBUTIONS OF L1 READING SUB-SKILLS TO L2 READING DEVELOPMENT IN ENGLISH AS A FOREIGN LANGUAGE AMONG SCHOOL-AGED LEARNERS - Dongbo Zhang; Keiko Koda (Universitas Katolik Indonesia Atma Jaya, 2008)
This study examined the cross-linguistic relationship in morphological awareness in two typologically diverse languages, Chinese and English and their relative contributions to L2 reading comprehension among Grades 5 and 6 students in China. Morphological awareness refers to the ability to analyze and identify a word’s morphological constituents. As such, this ability is believed to play a critical role in reading comprehension. Previous research suggests that the acquisition of morphological awareness necessitates substantial print exposure and experience. This implies that EFL learners may have difficulty in acquiring morphological awareness to its fullest extent. Theory of transfer posits, however, that once developed in one language, reading sub-skills, including morphological awareness, become available in learning to read in another language. This being the case, L1 morphological awareness, in principle, may compensate for restricted L2 print exposure in promoting L2 morphological awareness. Based on these insights, we hypothesized that (1) L2 morphological awareness would be closely related to L2 morphological awareness; (2) L1 morphological awareness is a stronger predictor of L2 morphological awareness than L2 print exposure; and (3) L1 morphological awareness facilitates L2 reading comprehension both directly and indirectly through L2 morphological awareness. These hypotheses were tested by measuring and comparing L1 and L2 morphological awareness and L2 reading comprehension. The results provide strong empirical support for the hypotheses. Their implications for EFL pedagogy are discussed. Keywords: Cross-linguistic relationship; Morphological awareness; Morphological constituents; Theory of transfer